Institutional dimensions of the just energy transition: reflecting the role of energy justice in public administration - Sokołowski, M. M.; Lauri, C.; Okem, Andrew E.; Olivera, B.; Tsuji, Y.; Mikusek, P. (Edinburgh University Press, 2023)
Climate policy-driven transformation processes in the energy sector are accelerating changes to both national and international legal frameworks. However, no successful just energy transition is achievable without significant regulatory reforms. In this context, the article examines the possibility for modifying and introducing regulatory tools to guarantee that the just energy transition is conducted in order to accomplish climate goals and lower anthropogenic greenhouse gas emissions into the atmosphere. The analysis is based on the application of the theory of energy justice and its five principal pillars: recognition, procedural, distributive, restorative, and cosmopolitan justice. For each of these five domains, the paper proposed regulatory tools that can strengthen the energy policies, both pursued and planned, in terms of institutional and decision-making dimensions. The analysis’ key conclusion is that there is a need for a fundamental change in how energy policies are planned and conducted, and that its regulatory tools must be modified to meet the requirements of energy justice. As a result, proposed in this paper are universal measures to institutionalise energy justice in different legal regimes that should be viewed as advancements in the effort to make energy transition processes more just.